"Eleven of us think he's guilty": Utilizing 12 Angry Men to teach symbolic convergence theory. Issue 4 (2nd October 2021) - Walton, Justin D.
Abstract : Courses: Group and Team Communication, Communication Theory, Rhetorical/Media Criticism. Objectives: The aims of this single-class activity are to (1) illustrate the basic concepts, processes, and properties of symbolic convergence theory; (2) apply fantasy theme analysis to the decision-making practices of a zero-history group; and (3) critically consider the communicative implications of fantasy chaining in the development of a shared group consciousness.